Differentiation of Cardiac from Noncardiac Pleural Effusions in Cats using Second‐Generation Quantitative and Point‐of‐Care NT‐proBNP Measurements. (27th January 2016) - Hezzell, M.J.; Rush, J.E.; Humm, K.; Rozanski, E.A.; Sargent, J.; Connolly, D.J.; Boswood, A.; Oyama, M.A.
Abstract : Background: Pleural effusion is a common cause of dyspnea in cats. N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) measurement, using a first‐generation quantitative ELISA, in plasma and pleural fluid differentiates cardiac from noncardiac causes of pleural effusion. Hypothesis/Objectives: To determine whether NT‐proBNP measurements using second‐generation quantitative ELISA and point‐of‐care (POC) tests in plasma and pleural fluid distinguish cardiac from noncardiac pleural effusions and how results compare to the first‐generation ELISA. Animals: Thirty‐eight cats (US cohort) and 40 cats (UK cohort) presenting with cardiogenic or noncardiogenic pleural effusion. Methods: Prospective cohort study. Twenty‐one and 17 cats in the US cohort, and 22 and 18 cats in the UK cohort were classified as having cardiac or noncardiac pleural effusion, respectively. NT‐proBNP concentrations in paired plasma and pleural fluid samples were measured using second‐generation ELISA and POC assays. Results: The second‐generation ELISA differentiated cardiac from noncardiac pleural effusion with good diagnostic accuracy (plasma: sensitivity, 95.2%, specificity, 82.4%; pleural fluid: sensitivity, 100%, specificity, 76.5%). NT‐proBNP concentrations were greater in pleural fluid (719 pmol/L (134–1500)) than plasma (678 pmol/L (61–1500), P = 0.003), resulting in different cut‐off values depending on the sample type. The POC test had good sensitivity (95.2%) and specificity (87.5%) when using plasma samples. In pleural fluid samples, the POC test had good sensitivity (100%) but low specificity (64.7%). Diagnostic accuracy was similar between first‐ and second‐generation ELISA assays. Conclusions and clinical importance: Measurement of NT‐proBNP using a quantitative ELISA in plasma and pleural fluid or POC test in plasma, but not pleural fluid, distinguishes cardiac from noncardiac causes of pleural effusion in cats.